Jurnalisme Provokasi Berbasis SARA: Studi Kasus Pemilihan Umum Presiden 2019 - Madonna, Madonna (Pusat Kajian Keamanan Nasional (Puskamnas) Universitas Bhayangkara Jakarta Raya, 2019)
The activities of journalism that are determined by the conditions of the press and mass media in a country eventually give birth to journalism which contains many elements of provocation, so it is feared that the Indonesian Government will emerge the potential for security disturbances from the communication and information sector. Furthermore, reporting on conflict or SARA sentiments in legal and independent online media has to consider whether it has relations with security and political conditions in an area. Such a situation became the initial foundation of research on the Early Detection of Provocation Journalism Based on SARA Sentiment Ahead of General Elections in Indonesia. Textually and conceptually, provocation journalism is very easily captured by the audience (audience) both the motive and the purpose. Constructed news or opinions, manipulations or inserted provocation contents become stimulants for the sake of the formation of public opinion which in the end moves active and dynamic actions and reactions. Journalism provocation is the latest development of four theories about the press and power, namely Authoritarian Press Theory, Libertarian Press Theory, Social Responsibility Press Theory, and Soviet Communist Theory (Fred S. Siebert et al, 1986). Of course, this provocation research on journalism can be used as a new reference as well as consideration in the management of democratic security both in the country and in the world.